Distribution Pattern of Aphis gossypii and its Coccinellid Predator Menochilus sexmaculatus in the Chilli Ecosystem - F. X. Wagiman; M. Y. Hussein; Rita Muhamad; A. S. Sajap; A. Ismail (Jurnal Perlindungan Tanaman Indonesia, 1998)
A study on the distribution pattern of Aphis gossypii Glover and its coccinellid predator, Menochilus sexmaculatus Fabricius, was conducted in a chilli ecosystem at the experimental field of Universiti Putra Malaysia. The study had revealed that distribution of M. sexmaculatus positively correlated with its prey distribution. The patterns of lateral and vertical distribution of A. gossypii and M. sexmaculatus were categorized as a clumped pattern.